Effectiveness and safety of a novel topical depigmenting agent in epidermal pigmentation: an open-label, non-comparative study - Chandrashekar, B. S.; Shenoy, Chaithra; Narayana N., Lakshmi (International Journal of Research in Dermatology, 2018)
Background: Active compounds isolated from plants are known to inhibit melanogenesis without melanocytotoxicity. The aim of this study was to assess the effectiveness and safety of a cream containing a combination of niacinamide, glycolic acid, vitamin E acetate, kojic acid, soy isoflavones, arbutin, pterowhite, licorice and ascorbyl glucoside for the treatment of epidermal pigmentation. Methods: Sixty subjects (between 18-45 years) with epidermal pigmentation were enrolled in this 12-week, open-label, non-comparative study. Clinical/dermoscopic aspects (grade-1: <25%; grade-2: 25-50%; grade-3: 50-75%; grade-4: >75% reduction in the amount of epidermal pigment); melanin index/erythema measure (Dermacatch); extent, depth and density of pigmentation (FotoFinder) and safety were assessed. Results: Out of 60 enrolled subjects, 53 completed the study. Overall percentage of melanin and erythema improvement (Dermacatch) was 24.2% and 7.4% respectively (p<0.05). Based on Fotofinder images, 13% had grade 4 improvement, 47% had grade 3 improvement, 30% had grade 2 improvement while 9% subjects had grade 1 improvement. On the basis of clinical photographic images, 15% had grade 4 improvements in the skin colour, 41% had grade 3, 34% had grade 2 and 9% subjects had grade 1 improvement. Adverse effect of skin irritation was reported in one subject, which resolved after discontinuing the treatment. Conclusions: Cream containing a combination of niacinamide 4.0%, glycolic acid 2.0%, vitamin E acetate 0.1%, kojic acid dipalmitate 2.0%, soy isoflavones 0.5%, arbutin 2.0%, pterowhite 0.12%, licorice 40% CA 0.12%, ascorbyl glucoside 0.1% was found to be safe and effective in the treatment of epidermal pigmentation.